Мотиваційні аспекти побудови успішного бренду - Оксенюк, Катерина Ігорівна (Київ, 2025)
У статті досліджено мотиваційні аспекти побудови успішного бренду як важливий чинник забезпечення його конкурентоспроможності та стійкого розвитку в сучасному ринковому середовищі. Зазначено, що в умовах високої конкуренції та динамічних змін споживчих потреб традиційні інструменти брендингу поступаються місцем мотиваційним підходам, які ґрунтуються на глибокому розумінні поведінкових моделей споживача. Проаналізовано роль внутрішньої мотивації персоналу як ключового ресурсу формування автентичного та привабливого бренду. Зроблено акцент на необхідності комплексного підходу, який поєднує зовнішнє бренд-позиціонування з внутрішнім залученням працівників до реалізації цінностей бренду. Визначено ключові чинники, які впливають на лояльність споживачів, формування емоційного зв’язку з брендом і підвищення ефективності маркетингових комунікацій. Стаття поєднує теоретичні підходи до розуміння мотивації з практичними рекомендаціями щодо формування брендів, орієнтованих на цінності та довготривалі відносини з клієнтами

The article explores the motivational aspects of building a successful brand, highlighting their growing importance in the context of an increasingly competitive and dynamic market environment. The formation of a strong brand today requires more than product quality and advertising – it demands a deep understanding of consumer psychology, emotional engagement, and internal motivation of personnel. The research emphasizes that motivation is a key factor that influences both the formation of consumer loyalty and the internal corporate culture that supports and communicates the brand's values. The paper examines the dual role of motivation: on the one hand, as a mechanism for influencing consumer behavior and creating long-term emotional attachment to the brand, and on the other, as a tool for increasing employee engagement, which directly affects the brand’s internal strength and authenticity. Particular attention is paid to the integration of motivational strategies into the brand development process, including personalized marketing communication, value-based positioning, and employee branding practices. The author argues that motivational branding is not a separate element of brand strategy but its core, allowing businesses to build meaningful relationships with target audiences and differentiate themselves in oversaturated markets. The article presents key motivational factors that affect the perception of the brand, including emotional resonance, trust, identity alignment, and the feeling of belonging. It also identifies the impact of internal motivation on employee behavior, corporate communication, and the consistent delivery of brand promises. The research is grounded in interdisciplinary analysis, combining concepts from marketing, management, psychology, and behavioral economics. Based on the findings, the article offers practical recommendations for integrating motivational tools into brand-building strategies. The conclusions underline the need for a systematic and holistic approach to branding, in which motivation becomes a driver of both internal and external brand development.
Motivational aspects of building a successful brand
Keywords: мотивація; брендинг; стратегія; позиціонування бренду; успішний бренд; мотивація персоналу; лояльність споживачів